Practical displacement-based seismic design approach for PWF structures with supplemental yielding dissipators. (1st October 2018) - Sun, Tianshu; Kurama, Yahya C.; Ou, Jinping
Highlights: A displacement-based seismic design approach for the PWF system is proposed. Yielding dissipators significantly reduce the seismic response of PWF structures. The strength and stiffness designs of the pin-supported wall are proposed. Mid-height column ends connected to the dissipators have increased strength demands. Abstract: This paper analytically investigates the design of supplemental metallic yielding dissipators to reduce the lateral displacements of pin-supported wall-frame (PWF) structures under high-intensity ground motions. The PWF system involves the use of a base-pinned structural wall to impose a first-mode dominant lateral drift profile on the coupled frame. Supplemental dissipative devices can be applied to increase the energy dissipation capacity of the coupled system by utilizing the relative displacements at the vertical wall-to-frame connections. This study proposes a displacement-based seismic design approach to determine the dissipator parameters so that the maximum roof drift of the structure under severe ground motions can be reduced to an allowable target roof drift. The validity of the proposed approach is verified based on nonlinear dynamic time-history analyses of three PWF structures with yielding dissipators. Besides, procedures to determine the minimum wall stiffness and strength are suggested for the preliminary design of the pin-supported wall. The dynamic behaviors of the example structures are critically evaluated, indicating that PWF system is suitable for the seismic retrofit project as well as for the development of novel sustainable earthquake resisting system.